Hospitalization due to drug poisoning in under-five-year-old children in Minas Gerais/Brazil, 2009 – 2018 - Bego, Brendali Sorgon; Pereira, Mariana Linhares; Nogueira, Leilismara Sousa (Medicina (Ribeirao Preto), 2020)
Objective: Describe hospital admissions in the state of Minas Gerais due to drug intoxications in children under five years old between 2009 and 2018. Methods: descriptive-analytical survey study, with data from the National Hospital Information System (SIH/SUS); the drugs involved were categorized into therapeutic classes (ATC), and the data obtained were analyzed by descriptive statistics. Results: 1,888 hospitalizations were identified with 2,358 diagnoses of poisoning and three deaths; the most common therapeutic classes were unspecified drugs (47.54%); antiepileptic/sedative-hypnotics/antiparkinson drugs (14.72%); psychotropic drugs (6.62%); systemic antibiotics (4.88%); and non-opioid analgesics/antipyretics (4.75%). Conclusion: among the defined therapeutic classes, drugs that act in the Central Nervous System were the main agents causing drug intoxication. However, more studies are needed to analyze hospitalizations across the state since SIH/SUS only contemplates hospitalizations subsidized by SUS.